PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN OKEJEK : Studi Kasus: Pada Kecamatan Medan Perjuangan Kota Medan - Tri Melda Mei Liana (Majalah Ilmiah METHODA, 2021)
This study aims to determine the effect of service quality and price on Okejek's customer satisfaction (Case Study on the Medan Perjuangan District). The sample used in this study was 100 respondents using a questionnaire. From the results of multiple regression analysis, the service quality variable has a positive effect on customer satisfaction, the price variable has a negative effect on customer satisfaction. From the t-test results, the service quality variable is significant to customer satisfaction, the price variable is not significant to customer satisfaction. Based on the results of the F test, the variables of service quality and price together have a significant effect on customer satisfaction. From the results of testing the coefficient of determination R2, service quality and price variables can explain customer satisfaction of 66.4% while the remaining 33.6% is explained by variables not examined.